Completion Fluid dengan Nitrat - Formate Base - Nasution, Mohammad Mahlil (Jurnal Jaring SainTek, 2019)
Completion Fluid is a Liquid of Salt Solution (Brine), used during the Well Completion, also to Killing Well job, when doing Work Over Wells and Well Services Jobs and Fishing Job and also functions as Packer Fluid. Completion Fluid is generally used in Reservoir formations that are sensitive to Shales, Clay or other minerals. The purpose of using Completion Fluid is to avoid or reduce formation demage. The formation damage causes reservoir formation that has hydrocarbon potential, after being drilled and produced the flow of oil becomes small and even difficult to flow. Formation damage need to be given very serious attention so that the Oil production in our country can increase significantly because the impact is that production does not increase significantly, Cost of production is high. If an effort to minimize damage is done optimally, it is expected that production will increase significantly so that the production target from year to year can be achieved. This invention relates to the method of making Completion Fluid for Drilling, Work Over and Well Services as Drilling activities in the Oil and Gas industry, using fresh water and solids as the material, more specifically is a solid which is a soluble solid as a base formula for making the fluid. In this case, the basic material of the solid material used for completion fluid is Nitrate and Alkali Formate. This completion fluid can reach SG (Specific Gravity) up to 2.0. This completion fluid has very low corrosivity (Corrosivity), which is stable at very high temperatures and high pressures.